Description of a new species of Helina Robineau-Desvoidy (Diptera, Muscidae) from the Rhodope Mountains of Bulgaria. - Zielke, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Helina momchili spec. nov. is described from the Rhodope Mountains in Bulgaria and compared to similar species known from the Palaearctic Region.KeywordsHelina momchili spec. nov., comparison, Bulgaria.Nomenclatural Actsmomchili Zielke, 2016 (Helina), spec. nov.